2018
DOI: 10.1111/avsc.12363
|View full text |Cite
|
Sign up to set email alerts
|

Soil properties and neighbouring forest cover affect above‐ground biomass and functional composition during tropical forest restoration

Abstract: Questions:We studied the importance of soil properties and neighbouring forest cover in affecting plant community biomass and assembly during the tropical forest restoration process. We also investigated how compositional responses depended on traits expected to influence individual success.Location: Forest restoration sites across anthropogenic grasslands in mixed use agricultural watersheds, eastern São Paulo state, Brazil. Methods:We identified and measured all woody individuals (DBH ≥ 5 cm) in four 200-m² … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 57 publications
(70 reference statements)
1
23
1
3
Order By: Relevance
“…In addition, the very low Al, P, Ca, and Mg backgrounds on lowland Atlantic forest soils suggest they are resistant and K resilient to human‐induced disturbances, in cases where sites were left to regenerate naturally and were not subsequently used or disturbed. Although some studies have shown that soil with very low nutrient availability can limit the absorption of nutrients and the regeneration of secondary forests (Pinho et al., ; Toledo et al., ; Wang & Houlton, ), we show that the deep‐weathered sandy soils of lowland Atlantic forests might not act as a filter for natural vegetation recovery (see Toledo et al., ). Therefore, our findings have potentially important implications for passive restoration projects (Mendes et al., ), as they reflect the ability of the lowland Atlantic forest to recover naturally over time, following disturbance or field abandonment, without requiring active regeneration or soil management (Chazdon et al., ; Crouzeilles et al., ; Poorter et al., ).…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…In addition, the very low Al, P, Ca, and Mg backgrounds on lowland Atlantic forest soils suggest they are resistant and K resilient to human‐induced disturbances, in cases where sites were left to regenerate naturally and were not subsequently used or disturbed. Although some studies have shown that soil with very low nutrient availability can limit the absorption of nutrients and the regeneration of secondary forests (Pinho et al., ; Toledo et al., ; Wang & Houlton, ), we show that the deep‐weathered sandy soils of lowland Atlantic forests might not act as a filter for natural vegetation recovery (see Toledo et al., ). Therefore, our findings have potentially important implications for passive restoration projects (Mendes et al., ), as they reflect the ability of the lowland Atlantic forest to recover naturally over time, following disturbance or field abandonment, without requiring active regeneration or soil management (Chazdon et al., ; Crouzeilles et al., ; Poorter et al., ).…”
Section: Discussioncontrasting
confidence: 58%
“…Depending on the intensity and frequency of the disturbance, soil properties can be negatively affected leading to soil degradation via increased erosion, compaction, sealing, leaching, salinization, acidification, and nutrient losses (Lal, ; Oldeman, ). In this case, forest productivity and ecosystem functions are also affected and, ultimately, the capacity of the ecosystem to recover after disturbance (Chazdon, ; Pinho et al., ; Toledo, Perring & Verheyen, ; Wall, ). For these reasons, deforestation and degradation of tropical forests are especially harmful to the environment and ecosystem functioning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we did not directly address the causes of species differences between sites, our results suggest that soil fertility and texture may play an essential role. In fact, other studies have documented that poor soils with a greater percentage of sand are not favorable to aboveground biomass accumulation (Toledo et al ) and that low nutrient availability is the dominant abiotic factor limiting the growth of young trees (Mayoral et al ).…”
Section: Discussionmentioning
confidence: 99%
“…For sampling vegetation and soil attributes, the size of each plot was 500 m 2 (50 m long and 10 m wide), a total area of 2000 m 2 for each site. The size and number of plots were chosen according to similar investigations aimed at evaluating vegetation structure and composition in tropical forest restoration projects [40][41][42].…”
Section: Experimental Designmentioning
confidence: 99%